Commuting for Symbolic Capital. Narratives of Location and Positionality of Palestinian Refugees - Rasmussen, Lene Kofoed (Women, Gender & Research, 2007)
A sense of marginalisation among Palestinian refugees in Denmark seems to be connected to a lack of recognition of their lifestyle which is diffuse and difficult to cope with. Thus, the pertinence of symbolic capital for emotional forms of belonging is uncovered in transnational practices and narratives on family and gender relations among Palestinian refugees.